ENHANCING ACTIVITIES TYPES OF TEACHERS USING COOPERATIVE JIGSAW IN CLASS VIA - Nayuk Sestuningsih; Dwi Kameluh Agustina; Minto Santoso (JOSAR (Journal of Students Academic Research), 2019)
Application of jigsaw cooperative learning is done to increase the activity of teachers. The method used is qualitative descriptive method to describe the condition of the activity of teachers in the learning theme 8 sub themes 1. This type of research is "Classroom Action Research" or the classroom action research (PTK). This study was conducted using two cycles. The procedure of research include: (1) planning, (2) implementation, (3) observation (4) evaluation and (5) result. The technique of collecting data through observation / observation of teacher activities that take place in two cycles at the end of the lesson. The conclusion of this study is, activity increased teachers who in turn have an impact on student learning outcomes also increased.